Exploring the Experiences During Teaching Internships in Indonesia and Thailand: Perspectives on Intercultural Skills - Maesaro, Maesaro; Wijirahayu, Suciana (Jetlal, 2025)
Abstract This study investigates the internship experiences of English Education students from UHAMKA in Indonesia and Thailand, focusing on how these experiences shape their teaching skills and cultural understanding. Despite the growing importance of teaching English as an international language, there is limited research comparing the internship experiences of students in different cultural contexts, particularly in Indonesia and Thailand. The purpose of this study is to explore how multicultural internship experiences influence students’ confidence in teaching and their intercultural skills. A mixed methods approach was employed, utilizing Likert-scale questionnaires and open-ended questions to gather data from 34 students who completed internships in both countries. The results indicate that 85.3% of participant reported increased confidence in their teaching abilities. Challenges such as language barriers and differing teaching methodologies were identified, yet students emphasized the importance of cultural adaptation and experiential learning. The findings highlight the significance of practical internship experiences in enhancing teaching readiness and intercultural competence, ultimately preparing future educators to thrive in diverse educational settings.